Some peculiarities of perceptive thinking of the 6th-form schoolchildren - Kulvičienė , A. (Psichologija, 1971)
Perceptive thinking is the remaking of the sensual material in the process of immediate perception of the environment. The aim of the study is to show some peculiarities of perceptive comparison in botany learning process of the 6th-form schoolchildren. The data obtained showed that the schoolchildren are able to discern various similarity and difference relations of the objects but they have some difficulties in discerning their similarity.